Amino-functionalized Ti3C2 MXene as efficient additive for high-performance methylammonium-free inverted perovskite solar cells - Rossato, Jessica H.H. [UNESP]; Lemos, Hugo G. [UNESP]; Gouvea, Igor Coelho; Lounasvuori, Mailis; Nandayapa, Edgar; Tarasov, Alexander; Tomic, Maja; Santos, Sydney F.; Stavale, Fernando; Unger, Eva; Graeff, Carlos F.O. [UNESP] (Elsevier, 2025)
The Ti3C2Tx MXenes are promising additives for perovskite absorber layer due to their changeable work function (WF) and favored affinity to under-coordinated ions. These features can be further tuned by inserting alternative functional groups other than oxygen and fluorine commonly present in these 2D materials. In this work, we use amino functionalized Ti3C2Tx (MXN) as effective additive for a methyl-ammonium free perovskite in p-i-n devices. Amino groups demonstrate to increase the interaction of MXenes with under-coordinated ions and to reduce WF of perovskite films. These features contribute to mitigate non-radiative recombination and to increase charge carrier lifetime and density of photogenerated charges, reflecting in better Voc and Jsc. These improvements lead to devices with optimized efficiency of 21.33 ± 0.31 % (22.84 % for the champion device). The MXN also increase device stability which lasted about four times more under ISOS-L2 protocol. In situ photoluminescence spectrum monitoring during perovskite coating indicates that MXN acts as nucleating sites for bromine-rich intermediate phases at the early stages of the perovskite formation. The MXN also provides additional carrier charges passivating intrinsic defects generally formed by anions diffusion during the halide homogenization process.